On new exact solutions of a nonlinear diffusion system that describes the growth of protein crystals - Cherniga, R. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
By using the method of additional generating conditions, we construct multiparameter families of exact solutions of a nonlinear diffusion system that describes the growth of protein crystals. We demonstrate the efficiency of the application of the solutions obtained to the solution of the corresponding nonlinear problem with moving boundary.